How can multi-criteria analysis support deliberative spatial planning? A critical review of methods and participatory frameworks. (October 2021) - te Boveldt, Geert; Keseru, Imre; Macharis, Cathy
In spatial planning, the paradigm has shifted from positivist to deliberative approaches. Still, cost–benefit analysis remains the dominant evaluation method. Multi-criteria analysis is arguably more appropriate, as it allows for stakeholder participation. While there are dozens of ever more sophisticated multi-criteria analysis methods, their practicality as real-world learning tools has received little attention. The goal of this article is to assess the suitability of different multi-criteria analysis methods for deliberative planning. It presents a critical review of the logical-mathematical cores of the principal methods but also of the different participatory frameworks within which they can be applied. While mathematically sophisticated methods are valuable in well-defined problems with precise data available, we conclude that in the participatory and politically sensitive stages of the planning process, user-friendly and transparent methods are more appropriate and recommend the development of a method that supports the incremental improvement of design options rather than ranking alternatives.